2018
DOI: 10.1007/s00261-018-1600-6
|View full text |Cite
|
Sign up to set email alerts
|

Short-term reproducibility of radiomic features in liver parenchyma and liver malignancies on contrast-enhanced CT imaging

Abstract: A greater number of liver malignancy radiomic features were reproducible compared to liver parenchyma features, but the proportion of reproducible features decreased with increasing variations in contrast injection rates and pixel resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 35 publications
(27 reference statements)
3
29
0
Order By: Relevance
“…The spatial variations in image brightness may be enhanced by the intravenously injected contrast agent, which may then result in the variability of radiomics features. This is supported by the findings of previous studies, which suggested that hepatic texture parameters correlate with hepatic vascularity [32], and the proportion of reproducible radiomics features decreases with the increasing variations in contrast injection rates in liver cancer patients [21]. Therefore, our study indicated that radiomic features may be affected by the phase (arterial or venous) of acquisition, and the reproducibility and stability of radiomics features due to image acquisition should be investigated extensively before using these features for classifying models.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The spatial variations in image brightness may be enhanced by the intravenously injected contrast agent, which may then result in the variability of radiomics features. This is supported by the findings of previous studies, which suggested that hepatic texture parameters correlate with hepatic vascularity [32], and the proportion of reproducible radiomics features decreases with the increasing variations in contrast injection rates in liver cancer patients [21]. Therefore, our study indicated that radiomic features may be affected by the phase (arterial or venous) of acquisition, and the reproducibility and stability of radiomics features due to image acquisition should be investigated extensively before using these features for classifying models.…”
Section: Discussionsupporting
confidence: 88%
“…Previous research [20] indicated that contrast-enhancement could affect the performance of radiomic models in diagnosing solitary pulmonary nodules. For example, Perrin's study [21] also showed that the proportion of reproducible features decreases with the increasing variations in contrast injection rates in liver cancer patients who underwent consecutive CECTs. In diagnostic radiology, a large proportion of CT images are contrast-enhanced.…”
Section: Introductionmentioning
confidence: 98%
“…In lung cancer, the diagnostic performance of a radiomic signature for solitary pulmonary nodules fluctuates based on slice thickness, contrast enhancement, and the convolutional kernel [196]. Changes in pixel resolution and contrast injection rates decreased the proportion of reproducible features in liver cancer [197]. Reproducibility testing is becoming more routine in the radiomic biomarker identification process [187,[198][199][200][201][202][203].…”
Section: Reproducibility Of Radiomic Featuresmentioning
confidence: 99%
“…In general, CT-based radiomics studies have shown that the variation of image acquisition parameters such as slice thickness, reconstruction algorithms, image resolution, contrast medium, and scanner type has the most significant influence on texture quantification [9][10][11]. In particular, reconstruction algorithms, pixel resolution, changes in contrast injection rates, and scanner models have been specifically implicated in HCC radiomics [9,10,12]. Regarding slice thickness, thinner image slices (1.25 and 2.5 mm) yield more quantitative texture information than thick slices (5 mm) [11].…”
Section: Ct-based Radiomicsmentioning
confidence: 99%